THE USING OF COMIC AS A TEACHING MATERIAL IN BUILDING CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Lubis, Maulana Arafat (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
Education is capable to develop a country. One of the techniques is by using appropriate teaching material. In addition, the using of teaching material ought to appropriate with particular topic. Teaching material also ought to arranged sistematically in order to create the fun learning atmosphere. Horsley, Knight, dan Huntly, (2010: 45) state a good quality of teaching material has substansial contribution to students quality in learning experience and outcome. Teaching material conveys electronic and non-electronic that contain the information to gain student’s knowledge due to reaching the learning objectives. (Sitepu, 2014:183). Comic is  one of efective teaching material that is used in scholl especially in Elementary school. It is suggested because comic contain pictures and stories with characteristic that able to build students’ character. Consequently, teaching material through comic has significant role in improving student’s ability and education quality in Elementary School